An unusual and malignant intussusception in a child. Issue 1 (December 2016) - D'Angelo, Gabriella; Marseglia, Lucia; Manti, Marta; Stroscio, Giovanni; Impollonia, Daniela; Arena, Salvatore; Impellizzeri, Pietro; Salpietro, Carmelo; Romeo, Carmelo; Gitto, Eloisa
Abstract Intussusception is a common cause of bowel obstruction in the pediatric population. Malignant lesions account for up to 30 % of all cases of intussusception in the small intestine. We herein report an interesting case of ileo-colic intussusception caused by diffuse large B-cell lymphoma, in a child. The patient underwent laparoscopic right hemicolectomy. Pathologic evaluation revealed a diffuse large B-cell lymphoma. In cases of intussusception, especially in the older age group of children, a high index of suspicion for malignant lymphoma of the bowel should be observed.